Mantenimiento de cruzas dialélicas y evaluación de 10 familias de la variedad criolla de maíz suave “blanco de leche” (Zea mays l.) en la granja experimental Naguan de la Universidad Estatal de Bolívar - Cando Curi, Edison Eduardo (2021)
Maize cultivation worldwide is very important for the great genetic combinatorial variability, diversity of uses within the Value Chain and for its contribution to food security and sovereignty. Soft maize in the high land of Ecuador is the main component of production systems and in Bolivar province contributes 60% of ingress in the Agricultural Production Unit (APU). However, due to many adverse biotic and abiotic factors the Improved and Criollas varieties, they are being severely affected by climate change and there are also new demands by consumers especially for maize “Blanco de Leche” cultivars. This research was carried out for the fourth cycle at the Experimental Farm of Naguan of Bolivar State University in the parish of San Lorenzo located at an altitude of 2604 m. The objectives were: (i) To evaluate the agronomic adaptation of 10 families of the native variety of maize "Blanco de Leche" selected in the previous three cycles. (ii) Perform the Dialectical Crosses of 10 families, selected in the previous three cycles from plant to plant and iii) Compare the agronomic behavior of the families and the corresponding crosses. Models Griffing model II was applied for genetic analysis and Duncan's variance and Multiple Range test analyses were performed for the quantitative agronomic variables of the 10 families; Kolmogorov-Smirnov normality tests, Levene variance homogeneity, t Studen test, and Man Whitney's nonparametric U test to compare the medians of families with crossbreeding. Significant differences were obtained for the main agronomic components within families such as the growing cycle, health, number of cobs, length and diameter of cobs and weight per plot. According to Griffing dialectic analysis model and the different statistical tests of normal distribution, variance homogeneity test, and man Whitney's non-parametric U-sample test and comparing the mean and medians of the 10 families with their corresponding crosses, the results were different, with a reduction in crossbreeding of 60% in the total number of cobs per plot and 63.73% of the field weight, which were mainly affected by genetic factors (combinatorial aptitude),crossbreeding and environmental skills such as drought stress, heat and strong winds. Finally, this study showed that the Half Brothers Selection technique of the four-cycle participatory improvement process was more efficient than the crosses performed.